EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK DISKUSI KELOMPOK UNTUK MENINGKATKAN KEMAMPUAN ASERTIF SISWA KELAS X SMK NEGERI 4 KOTA BENGKULU - Sekar Ayu Larasati; Elita, Yessy; Sinthia, Rita (UNIVERSITAS BENGKULU, 2025)
This study purposed to describe the level of differences in the assertive ability of the control group and the experimental group before and after participating in group guidance activities and to describe the effect of using group discussion techniques on the level of assertive behavior of class X students of SMK Negeri 4 Bengkulu City. This research method uses the pretest- posttest control group design method. The sampling technique for students in class X RPL 1 and RPL 2 used random sampling and obtained 9 students. Data collection techniques using a questionnaire with a Likert scale. Research data analysis techniques using the T test (paired sample test). The results obtained in the study showed an increase in assertive behavior in the experimental group after being given group guidance services using group discussion techniques. This can be seen from the results of testing the hypothesis with the results of texperiment = -10,845 p = 0.000 p<0.05. While the results of tcontrol = -1.895 p = 0.095 p>0.05 so that Ho is rejected and Ha is accepted. This means that there is a significant effect of group guidance services on the experimental group with group discussion techniques increasing the assertive behavior of class X students of SMK Negeri 4 Bengkulu City.Keywords : Assertive Ability, Group Guidance Service, Group Discussion